2015
DOI: 10.3390/ijerph121012466
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Evaluation of e-Liquid Aerosol using Different Lung-Derived Cell Models

Abstract: The in vitro toxicological evaluation of e-liquid aerosol is an important aspect of consumer protection, but the cell model is of great significance. Due to its water solubility, e-liquid aerosol is deposited in the conducting zone of the respiratory tract. Therefore, primary normal human bronchial epithelial (NHBE) cells are more suitable for e-liquid aerosol testing than the widely used alveolar cell line A549. Due to their prolonged lifespan, immortalized cell lines derived from primary NHBE cells, exhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 11 publications
5
60
2
Order By: Relevance
“…In contrast with previous studies, we did not detect significant changes in FeNO 5,23 . This may be due to the short time of exposure or the small number of observations.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast with previous studies, we did not detect significant changes in FeNO 5,23 . This may be due to the short time of exposure or the small number of observations.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, lung function impairment, as reflected in Raw and sGaw, was demonstrated regardless of the nicotine concentration of the e-cigarette. As animal models have indicated negative effects after exposure to e-cigarette liquids containing aromatics 5,33 , it would be of interest to test the effect of these constituents in humans in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cellular studies, exposure to ENDS vapor increased anti-inflammatory processes, 275,278 placed oxidative stress on exposed cells, 269,279,294,301 and increased cell apoptosis and necrosis. 305 Particular ENDS flavors are more cytotoxic than others, but generally most studied ENDS liquids are much less cytotoxic than cigarette smoke extract.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…(Bahl et al 2012;Romagna et al 2013;Cervellati et al 2014;Willershausen et al 2014;Scheffler et al 2015aScheffler et al , 2015bSchweitzer et al 2015;Tartell 2015). Hom et al (2016) also reported platelet activation, aggregation, and adhesion under EC vapour extracts in vitro.…”
Section: Cellular Level Effectsmentioning
confidence: 99%